The association between circulating MicroRNA‐150 level and cholangiocarcinoma - Salem, Perihan El Sayed; Ghazala, Rasha Abdelmawla; El Gendi, Ahmed Mohamed; Emara, Doaa Mokhtar; Ahmed, Nesma Mahmoud (Journal of clinical laboratory analysis, 2020)
Cholangiocarcinoma (CCA) is a rare tumor which requires a multimodality approach for its diagnosis. Carbohydrate antigen 19‐9 (CA19‐9) is currently the most commonly used tumor marker for CCA; nevertheless, it has certain limitations which need to be considered when using it as a tumor marker. MiRNA‐150 altered expression has been linked to the development and tumorigenesis of several cancers including CCA. This work aimed to study the serum level of CA19‐9 and miRNA‐150 expression in CCA patients and, also, to correlate their levels with tumor staging and different studied clinical and laboratory parameters. This work included 35 patients with CCA who were admitted to Hepatobiliary Unit, Alexandria Main University Hospital (Group I). Also, 35 age‐ and sex‐matched healthy subjects were included as a control group (Group II). All included subjects were submitted to measurement of serum CA19‐9 and MiRNA‐150 expression levels. Serum CA19‐9 levels showed an evident high median among CCA patients, while serum miRNA‐150 expression levels were evidently low among those patients. Moreover, combining miRNA‐150 with CA19‐9 made the accuracy of diagnosis of CCA much more reliable. Thus, miRNA‐150 can be considered as a non‐invasive, sensitive serum biomarker for the diagnosis of CCA especially when combined with CA 19‐9.